1993
DOI: 10.1007/bf02319012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tissue culture and whole plant responses to salinity in potato

Abstract: Salt sensitivities of six potato cultivars using six levels of sodium chloride (0.0 to 0.25M) were studied in a greenhouse. Responses of these cultivars were also determined in tissue culture by studying rooting of stem segments, increase in length of cultured roots and inhibition of growth of cell suspension cultures using similar salt concentrations. Responses of cultured stem segments and cell suspensions differed from those expressed by whole plants. A close similarity was observed between the salt stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Farhatullah et al (2002) reported that even at 1% NaCl in the media suppressed the root growth of the tested potato vari eties [26]. NaCl at 100 mM inhibited root growth in potato which was also agreement with our findings [15]. The growth of the potato cultivars in different parameters was significantly influenced by the interaction of cultivars and concentrations of NaCl ( Table 2).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Farhatullah et al (2002) reported that even at 1% NaCl in the media suppressed the root growth of the tested potato vari eties [26]. NaCl at 100 mM inhibited root growth in potato which was also agreement with our findings [15]. The growth of the potato cultivars in different parameters was significantly influenced by the interaction of cultivars and concentrations of NaCl ( Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…A small number of potato genotypes have been reported in salinity tolerance under outdoor, greenhouse or in vitro conditions. Field trials [8,9,10,11] and greenhouse pot trials were used to examine salinity tolerance genotype under NaC1 or sodium salt irrigation solutions based on either tuber yield [12,13], a relative reduction of foliage dry weight [14] or haulm fresh weight [15]. Conventional screening methods for the development of salt tolerant variants are laborious and time-consuming [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plant height, growth and water content have also been used as indices of salt stress in other studies of potato (Levy 1986;Levy et al 1988;Ashraf 1994;Gong et al 1996). Salt tolerance of six potato cultivars was closely related to relative growth rates of the roots following exposure to the salt stress (Naik and Widholm 1993). A positive relationship between root fresh weight and salt stress tolerance was also observed for ten potato clones exposed to salt stress in vitro and in the field (Morpurgo 1991).…”
Section: Introductionmentioning
confidence: 72%
“…Five genotypes of potato (Solanum tuberosum L.) viz., Kufri Badshah, Kufri Ashoka, Kufri Sindhuri, Kufri Lauvkar and Kufri Jawahar were selected for genetic transformation. Shoots of these genotypes were grown and maintained in tissue culture as described earlier (Naik & Widholm, 1993). Internodal stem segments (5-6 mm long) from 20 day old in vitro plants were placed on sterile filter paper discs (Whatman No.I) layered on Murashige & Skoog (MS) basal medium (1962) in Petri dishes and were incubated for 2 days at 25+1 ~ and 16 h photoperiod of 30 laE m -2 s -t light intensity.…”
Section: Construction Of Plant Transformation Vectormentioning
confidence: 99%